International Portfolio Investments in Central and Eastern European Countries - Stamenova, Radostina (Research Papers, 2021)
The paper aims to identify the factors which determine international portfolio investments in Central and Eastern European countries. The study was performed using a multivariate regression analysis of panel data, covering 11 countries in the period 1999-2018. The results show that the change in global risk factor has the strongest impact on IPI in the analysed group of countries. Other statistically significant determinants include EU membership, currency risk, government debt and stock market capitalization.
Keywords: International portfolio investment; Central and Eastern Europe; Panel data analysis